2016
DOI: 10.5935/abc.20160091
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Lipid Profile in the ELSA-Brasil Study

Abstract: BackgroundRegular physical activity (PA) induces desirable changes in plasma levels of high- and low-density lipoproteins (HDL and LDL, respectively) and triglycerides (TG), important risk factors for cardiometabolic diseases. However, doubts whether intensity and duration have equivalent benefits remain.ObjectiveTo assess the association of PA intensity and duration with HDL, LDL and TG levels.MethodsCross-sectional study with 12,688 participants from the Brazilian Longitudinal Study of Adult Health (ELSA-Bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
30
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 37 publications
6
30
0
7
Order By: Relevance
“…Study found that the reduction in TG levels was associated with higher physical activity intensity, but not with physical activity frequency [37]. Another study reinforced the benefits of physical activity on HDL and TG levels, with a slight advantage for vigorous physical activity as compared to physical activity duration of 150 min/week [39]. In our study, occupational physical activity intensity was used to access the status of physical activity and could provide approximations of ideal, intermediate, and poor physical activity recommended by the AHA.…”
Section: Discussionmentioning
confidence: 99%
“…Study found that the reduction in TG levels was associated with higher physical activity intensity, but not with physical activity frequency [37]. Another study reinforced the benefits of physical activity on HDL and TG levels, with a slight advantage for vigorous physical activity as compared to physical activity duration of 150 min/week [39]. In our study, occupational physical activity intensity was used to access the status of physical activity and could provide approximations of ideal, intermediate, and poor physical activity recommended by the AHA.…”
Section: Discussionmentioning
confidence: 99%
“…Initially, it was observed that Mb pre-MDT patients (n = 8) compared to healthy controls (n = 12) presented reduced HDL-cholesterol concentrations with values varying between 21-39, min-max mg/dL. A worrying fact, since the Brazilian Longitudinal Multicentric Study of Adult Health (ELSA Brazil) [55] classified as desirable levels of HDL-cholesterol �40 mg/dL for men and �50 mg/dL for women. These data are in agreement with recent findings from Silva et al (2018) and Negera et al (2018), which also observed lower levels of HDL-cholesterol in Mb patients compared to Pb and HC [56,57].…”
Section: Discussionmentioning
confidence: 99%
“…Lipid profile Omega 3 fatty HDL-c levels [102] More exercise is associated with smaller HDL-P, fewer large HDL-P and reduced mean HDL-size [130] TNF-α inhibitors TC and HDL-c levels [131] Omega 3 fatty circulating oxidized LDL-c [105][106][107] Correlation between the intensity of physical activity and HDL levels [132] 3 months anti-TNF-α treatment TC levels [133] DHA and EPA LDL particle size in hypertensive type 2 diabetes patients and with a hypertriglyceridemia [103,104] Inverse correlation between the intensity of physical activity and TG and LDL levels [132] TNF-α inhibition anti-inflammatory properties of HDL-c [134] Table 2. Cont.…”
Section: Dietary Lipids Physical Activity Therapymentioning
confidence: 99%
“…Further work should be performed to explore the relevance of multimodal strategies, including the consideration of other nutrients such as protein but also physical activity and/or specific medications (Table 2). Physical activity is known to improve TG and HDL-c serum levels [132], and helps to preserve lean body mass, muscle anabolic response and muscle function in RA patients [136][137][138]. On the other hand, an optimized protein intake seemed to have beneficial effects on muscle protein metabolism, muscle mass and quality.…”
Section: Perspectives: Multimodal Approachesmentioning
confidence: 99%